2019
DOI: 10.1080/1331677x.2019.1629978
|View full text |Cite
|
Sign up to set email alerts
|

The drivers of global value chain (GVC) participation in EU member states

Abstract: Integration within the EU single market increases the interconnection and interdependence of the EU economies. Global value chain (GVC) participation has become one of the most widely used indicators to measure the dispersion of the production process among different countries. The EU member states rate differently in the GVC participation index. The highest participation is in Luxembourg and Slovakia and the lowest is in Croatia. The aim of this paper is to identify the most important variables that influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 33 publications
(26 reference statements)
0
7
0
4
Order By: Relevance
“…(3) (4) ployment, exports and GDP were exogenous in the short term. However, the FDI variable adjusts to the long-run equilibrium and is statistically significant (see Kersan-Škabić, 2019).…”
Section: Vecm Modelmentioning
confidence: 99%
“…(3) (4) ployment, exports and GDP were exogenous in the short term. However, the FDI variable adjusts to the long-run equilibrium and is statistically significant (see Kersan-Škabić, 2019).…”
Section: Vecm Modelmentioning
confidence: 99%
“…Scholars have investigated the effect of PTAs on intermediate trade from GVCs perspective and found that PTAs can facilitate supply chain activity. When decomposing bilateral trade into different components, they mainly focus on the average effect of PTAs on GVCs (using a dummy variable to measure PTAs) and the effect of provisions related to services, investment, and competition on GVCs [30][31][32]. Starting from the product-based coverage of PTAs and testing its effect on different types of trade is meaningful in the global production network.…”
Section: Plos Onementioning
confidence: 99%
“…Arus investasi asing serta diversifikasi produk ekspor mendorong backward participation pada wilayah ECOWAS (Economic Community of West African States) (Tinta, 2017), sedangkan pada wilayah Uni Eropa pada umumnya lag partisipasi GVC, PDB perkapita serta pertumbuhan PDB memberikan dampak yang positif dan signifikan. Perbedaan terjadi jika dikelompokkan pada anggota baru Uni Eropa, penelitian dan pengembangan serta intensitas arus investasi asing mempengaruhi partisipasi GVC sedangkan arus investasi asing tidak terlalu berpengaruh pada Uni Eropa secara keseluruhan (Kersan-Škabić, 2019). Penelitian tersebut menunjukkan bahwa faktor yang mendorong partisipasi GVC memiliki perbedaan pada tiap wilayah karena perbedaan struktur ekonomi, geografi dan tingkat kemajuan suatu wilayah.…”
Section: Gambar 1 Tingkat Partisipasi Gvc 6 Negara Aseanunclassified